An Agenda for Research on Urbanization in Developing Countries : A Summary of Findings from a Scoping Exercise - Annez, Patricia Clarke; Linn, Johannes F. (2012)
This paper assesses the state of research and examines priorities for future work in the area of urbanization and growth. This is done by reviewing and summarizing the findings of five scoping papers covering the following topics: urban poverty, the political economy of urban poverty, urban real estate and housing, urban infrastructure finance, and external assistance for urban development.